KONSEP PENDIDIKAN ISLAM MENURUT IBNU KHALDUN - Sunhaji Sunhaji (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Education to work for income, or the popular term now education for the sake of improving the quality of human resoource development, in the present context turned out to cause many problems such as the emergence of disparities in the various sectors of life. The gap between the number of jobs available to the realities of an abundant amount of labor. Ibn Khaldunâ€™s conception of education who was born around six hundred years ago seems to still actual today. The recent conception of human resources in the community is a formulation of Ibn Khaldunâ€™s conception that tries to combine between philosophy and education, Â sociology and education so that the concept of education is still used today, as well as the expectations of the community can be used as a tool to help him well in modern society. According to the result of education is human being can actualize science (reason) that has been held in all aspects of life, which he called the haqiqoh al-insaniyah or complete Indonesian man, according to the national education, and ahlaku al-karimah in the perspective of Islamic education.